Correlational Evaluation of Cost Management and Supply Chain Performance of Food and Beverages Firms in Port Harcourt - Cyril, Ibama Awoiyim; Okwandu, Gabriel A.; Adiele, Kenneth. C. (Archives of Business Research, 2021)
This study adopted a correlational investigation to examine the relationship between Cost Management and Supply Chain Performance of food and Beverages firms in Port Harcourt. The population for this study consists of seventeen (17) food and beverages firms in Port Harcourt. The researcher conducted a census study due to the small size of the population. However, a total of Eighty Five (85) top managerial staff of the firms constituted the respondents for the study. Furthermore, Eighty five (85) copies of the questionnaire were administered to the top managers of each of the 17 food and beverages companies while seventy (70) copies were retrieved and used for the study. The respondent’s demographics were analyzed by employing the measures of central tendencies and measures of dispersions. Correspondingly, the Pearson Product Moment Correlation was used in testing the study hypotheses in other to ascertain the relationship between the predictor variable (Cost Management) and the criterion variable (Supply Chain Performance).The result of the analysis revealed that Cost Management significantly influenced Supply Chain Performance of food and Beverages firms in Port Harcourt. Hence, the authors concluded that Cost Management significantly affect Supply Chain Performance and therefore recommended that the management of food and Beverages firms in Port Harcourt should adopt appropriate cost management strategies in other to increase their level of supply chain performance.